Preclinical study for the ameliorating effect of l-ascorbic acid for the oxidative stress of chronic administration of organic nitrates on myocardial tissue in high sucrose/fat rat model - Ahmed Mohsen Elsaid Hamdan; Zuhair M. Mohammedsaleh; Aalaa Aboelnour; Sherif M.H. Elkannishy (Elsevier, 2022)
Background: The therapeutic activity of Glyceryl trinitrate (GTN) is mainly regulated by liberating nitric oxide (NO) and reactive nitrogen species (RNS). During this biotransformation, oxidative stress and lipid peroxidation inside the red blood cells (RBCs) occur. Hemoglobin tightly binds to NO forming methemoglobin altering the erythrocytic antioxidant defense system. Aim: The principal objective of our research is to show the ameliorating effect of l-ascorbic acid for the deleterious effects of chronic administration of nitrovasodilator drugs used in cardiovascular diseases such as oxidative stresses and tolerance. Method: We studied some biochemical parameters for the oxidative stress using groups of high sucrose/fat (HSF) diet Wistar male rats chronically orally administered different concentrations of Isosorbide-5-mononitrate (ISMN) 0.3 mg/kg, 0.6 mg/kg and 1.2 mg/kg. Afterwards, we evaluated the role of l-ascorbic acid against these biochemical changes in cardiac tissues. Results: Chronic treatment with organic nitrates caused elevated serum levels of lipid peroxidation, hemoglobin derivatives as methemoglobin and carboxyhemoglobin, rate of hemoglobin autoxidation, the cellular levels of the pro-inflammatory cytokines marker (NF-κB) and apoptosis markers (caspase-3) in the myocardium muscles in a dose-dependent manner. Meanwhile, such exposure caused a decline in the enzymatic effect of SOD, GSH and CAT accompanied by a decrease in the level of mitochondrial oxidative stress marker (nrf2) in the myocardium muscles and a decrease in the serum iron and total iron-binding capacity (TIBC) in a dose-dependent manner. Concomitant treatment with l-ascorbic acid significantly diminished these changes for all examined parameters. Conclusion: Chronic administration of organic nitrates leads to the alteration of the level of oxidative stress factors in the myocardium tissue due to the generation of reactive oxygen species. Using l-ascorbic acid can effectively ameliorate such intoxication to overcome nitrate tolerance.